A infração sexual e as (im)possibilidades de reintegração social de adolescentes: cartografias de uma psicóloga na socioeducação - Luiza Regina Campos Dalpiaz (2024)
This study examines the possibilities and limitations in the reintegration process of adolescents who have committed sexual offenses, including cases of sexual abuse against vulnerable individuals, within the framework of open socio-educational measures. Drawing from my professional experience as a psychologist in the Social Protection Service for Adolescents in Compliance with Socio-Educational Measures of Assisted Freedom and Community Service, I identified gaps in current practices, such as the automation of interventions, lack of community engagement, and insufficient attention to social markers, particularly those related to gender issues. Employing the Social Cartography method of Deleuze and Guattari, the research was structured into three complementary sections and two scientific articles. The sections address the relationship between youth, socio-educational measures, and sexual offenses against vulnerable individuals, emphasizing the importance of gender studies and highlighting the lack of research on this subject in the state of Mato Grosso do Sul. The first article, theoretical in nature, analyzes the influence of gender devices and patriarchy on sexual offenses against vulnerable individuals, as well as the potential roles of Psychology in this context, proposing interventions that denaturalize and de-pathologize such offenses. The second article adopts a critical performative autoethnography approach, utilizing Foucauldian concepts of discursive and confessional practices and regimes of truth, alongside Agamben’s concept of thanatopolitics, to discuss the ethical and political challenges of reintegrating these adolescents. By critically examining current socioeducational practices, the research aims to promote a more humanized and reflective approach, aligned with Baratta's critique and the questioning of the resocialization model proposed by Sinase. Thus, the study seeks to contribute to the debate on the reintegration of these youths, stressing the need for inclusive and dialogical practices in a context marked by power relations and marginalization.